Health Literacy in a Rural Clinic - Felecia Grier Wood (Rural Nurse Organization; Binghamton University, 2005)
Purpose: Health literacy is a critical prerequisite to effective self-management of any health problem. Nearly half of all adult U.S. citizens have difficulty with reading skills. For those living in rural areas who also experience health literacy deficits, self-management of health needs is doubly problematic. Rural dwellers are more likely to delay treatment for health problems and more likely to experience chronic health problems than their urban counterparts. The purpose of this research was to assess the health literacy of those seeking care in a rural health clinic. Design: The design of this descriptive study was a one-time survey using a convenience sample of 57 patients (89% Caucasian, 65% female) from a rural clinic in the southeastern United States. Data were collected in Fall 2003. Methods: The REALM (Rapid Estimate of Adult Literacy in Medicine) test and a demographic questionnaire were administered by trained nursing students to consenting patients as they arrived for clinic appointments. Data were analyzed descriptively and with non-parametric one-way ANOVA. Findings: The mean REALM score was 55.9 on a scale of 0 to 66. Half of the participants (n =29; 50.8%) read at the high school level, and 6 (11%) read at grade six or lower. Females scored significantly higher than males. The more difficult words included "impetigo," "colitis," "osteoporosis," and "diagnosis." Conclusions: Health literacy is a significant barrier to effective health care for many rural dwellers, particularly males. Health care providers can minimize the negative consequences of limited health literacy by assessing the literacy of their population and adjusting written and verbal communications accordingly.